α-lipoic acid decreases oxidative stress even in diabetic patients with poor glycemic control and albuminuria - Borcea, Valentin; Nourooz-Zadeh, Jaffar; Wolff, Simon P; Klevesath, Martina; Hofmann Bowman, Marion; Urich, Heinz; Wahl, Peter; Ziegler, Reinhard; Tritschler, Hans; Halliwell, Barry; Nawroth, Peter Paul (Free radical biology and medicine, 1999)
In the present cross-sectional study, the influence of α-lipoic acid on markers of oxidative stress, assessed by measurement of plasma lipid hydroperoxides (ROOHs), and on the balance between oxidative stress and antioxidant defence, determined by the ratio ROOH/(α-tocopherol/cholesterol), was examined in 107 patients with diabetes mellitus. Patients receiving α-lipoic acid (600 mg/day for > 3 months) had significant lower ROOHs and a lower ROOH/(α-tocopherol/cholesterol) ratio than those without α-lipoic acid treatment [ROOH: 4.76 ± 2.49 vs. 7.16 ± 3.22 μmol/l; p < .0001] and [ROOH/(α-tocopherol/cholesterol): 1.37 ± 0.72 vs. 2.16 ± 1.17; p < 0.0001]. In addition, the influence of glycemic control and albuminuria on ROOHs and on the ratio of ROOH/(α-tocopherol/cholesterol) was examined in the presence and absence of α-lipoic acid treatment. Patients were subdivided into three groups based on (1) their HbA1 levels (<7.5, 7.5-9.5, and >9.5%) and (2) their urinary albumin concentrations (<20, 20-200, and >200 mg/l). Neither poor glycemic control, nor the presence of micro- or macroalbuminuria prevented the antioxidant effect of α-lipoic acid. Using stepwise multiple regression analysis, α-lipoic acid was found to be the only factor significantly predicting low ROOHs and a low ratio of ROOH/(α-tocopherol/ cholesterol). These data provide evidence that treatment with α-lipoic acid improves significantly the imbalance between increased oxidative stress and depleted antioxidant defence even in patients with poor glycemic control and albuminuria.